The current discussion on Austrian family benefits - indicating a major dissensus on the interpretation of EU law - Balthasar, Alexander (Central European Public Administration Review, 2020)
In early 2018, Austria amended its family benefits law by introducing 'indexation' according to the average living costs of the country where the child actually resides. What seems to be, at first sight, a flagrant breach of EU law (in particular of Article 7 of Regulation EC 883/2004) is, when looking deeper, much more complicated and might very well be only a symptom of deeply rooted differences in the interpretation of current, post-Lisbon Union law, (i) in particular with regard to the relationship between the traditional prohibition of "discrimination on grounds of nationality" (Article 18 TFEU, Article 21(2) CFR; the 'Leitmotiv' of the Treaties) and the "citizenship of the Union" (Article 9 second sentence TEU, Article 20(1), first and second sentence) on the one hand and the further role of the "nationality of a Member State" on the other, which shall, pursuant to Article 9 TEU, third sentence, as well as Article 20(1) TFEU, third sentence, not be replaced by the "citizenship of the Union", (ii) but also with regard to Article 352 TFEU, the scope of which is, most probably, much smaller than that of its predecessor, Article 308 TEC, (iii) and last but not least, with regard to a proper understanding of the principle of equal treatment, requiring not to treat alike factually different situations. Giving a full picture not only in abstract terms but demonstrating the relevance of the said differences on the concrete example of the interpretation of the above mentioned secondary legislation, the author aims at contributing to bridging gaps and, thus, fostering a better mutual understanding as a vital precondition for the future legal cohesion of the EU.
Keywords: assessment of validity of EU law; Austria; Avstrija; citizenship of the Union; družinski prejemki; državljanstvo Evropske unije; family benefits; nacionalno državljanstvo; načeli enakega obravnavanja in nediskriminacije; načelo prenosa; nationality; otrokove pravice; presoja veljavnosti; principle of conferral; principles of equal treatment/non-discrimination; rights of the child; spremembe; Treaties amendment clauses; ustanovitvene pogodbe; zakonodaja EU